Дыхание калифорнийской щитовки (Quadraspidiotus perniciosus Comst.) (Insecta, Coccoidea) - Максимова, В.И. (Вестник зоологии, 1978)
Respiration of Quadraspidiotus perniciosus Comst was studied at different stages of ontogenesis. The lowest oxygen intake and respiratory coefficient were observed in larvae of age I at the diapausal state. Both indices grow in feeding specimens of Q. perniciosus. The highest level of gas exchange was observed in the insects just after moults and in a winged male.